Emergency versus elective ureteroscopic treatment of ureteral stones - Matani, Yousef S.; Al-Ghazo, Mohammed A.; Al-Azab, Rami S.; Bani Hani, Osamah; Ghalayini, Ibrahim F.; Bani Hani, Ibrahim (Canadian Urological Association Journal, 2013)
Introduction: This retrospective study investigates the role of the emergency ureteroscopic (URS) approach in the definitive treatment of ureteric stones. Methods: We reviewed all patients admitted for ureteric stones from May 2003 to December 2010. Those who underwent URS stone treatment were selected and stratified into emergency (EMG) and elective groups (ELG). Emergency URS is defined as URS being performed within 24 hours of admission to the emergency room. The main indication for emergency treatment was refractory ureteric colic in spite of narcotic analgesia. Both groups were statistically compared in terms of their patient-, stone- and outcome-related variables. The overall success rate was defined by the clearance of the stone and/or presence of residual fragments (<3 mm) at the end of 4-week follow-up period. Results: In total, 903 patients were suitable for analysis with 244 and 659 patients in the EMG and ELG, respectively. Age, sex and comorbidities were comparable in both groups. Average ages were 43.4 ± 15.31 and 45.6 ± 13.24 years among EMG and ELG, respectively. Stones had an average size of 0.92 ± 0.49 (in the EMG group) and 0.96 ± 0.53 cm (in the ELG group). We found that 61.1% and 65.7% of stones were distally located in the EMG and ELG, respectively. EMG had a longer operative time (69 ± 21.03 vs. 57 ± 13.45 minutes) with comparable average hospital stays (1.9 days). Intra-operative double-J stents or ureteric catheter insertion was noted in 72.5 and 67.7% of EMG and ELG, respectively. The overall complication rates were reported in 13.1% in EMG and 14.4% in ELG. A higher rate of ureteric injuries (early and late) was documented in the EMG group (7% vs. 5.6%). Most of these injuries were minor and manageable without additional procedure and/or general anesthesia. Success was achieved in 90.6% and 91.8% of the EMG and ELG groups, respectively. Conclusion: With recent advances in technology, the growing trend toward one-stage definitive treatment, patient acceptability and rising concerns over financial aspects, emergency URS treatment of ureteric stones is evolving as a standard initial management option.